2010
DOI: 10.1002/ijc.25162
|View full text |Cite
|
Sign up to set email alerts
|

miR‐193b is an epigenetically regulated putative tumor suppressor in prostate cancer

Abstract: AbstractmiRNAs have proven to be key regulators of gene expression and are differentially expressed in various diseases, including cancer. Our aim was to identify epigenetically dysregulated genes in prostate cancer. We performed miRNA expression profiling after relieving epigenetic modifications in 6 prostate cancer cell lines and nonmalignant prostate epithelial cells. Thirty‐eight miRNAs showed increased expression in any prostate cancer cell line after 5‐aza‐2′‐deoxycytidine (5azadC) and trichostatin A (TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 28 publications
3
97
0
Order By: Relevance
“…27 For example, a recent study suggested that miR-193b is epigenetically silenced in prostate cancer cells. 28 Several technical issues arise in studies of this nature. One is the choice of control for the comparison of expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…27 For example, a recent study suggested that miR-193b is epigenetically silenced in prostate cancer cells. 28 Several technical issues arise in studies of this nature. One is the choice of control for the comparison of expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…The promoter regions of miRNA genes are targets of a variety of epigenetic modifications, such as promoter hypermethylation or histone modifications. Several miRNAs have been shown to be silenced by promoter hypermethylation in urological tumors (23,24 ). Aberrant miRNA expression can also result from improper regulation by tumor-suppressor or oncogenic transcription factors.…”
Section: Mirnas and Signal Transductionmentioning
confidence: 99%
“…9,10 Changes in DNA methylation status have been implicated in cancer-associated miR deregulation. [11][12][13] As a single miR often inhibits numerous mRNAs within a defined biological pathway, understanding the epigenetic regulation of miRs in cancer might facilitate the development of new cancer therapies.…”
mentioning
confidence: 99%